Screening for atrial fibrillation in high-risk nursing home residentsKey Findings - Hassan A. Khan, MD; Nader Hanna, MD; Michael J. Chaskes, MD; Gregory D. Gudleski, PhD; Piotr Karmilowicz, BSc; Anne B. Curtis, MD, FHRS (Heart Rhythm O2, 2020)
Background: Various methods have been implemented for screening of patients for atrial fibrillation (AF), but the yield has generally been low. Targeting high-risk patients may improve detection of asymptomatic AF, which could be of value if appropriate treatment could be initiated before a potential thromboembolic event. Objective: The purpose of this study was to test screening of high-risk nursing home residents having ≥2 risk factors for AF and no previous history of AF using a smartphone-based electrocardiographic (ECG) monitoring device to determine whether it is an accurate, easy-to-use method of screening for asymptomatic AF. Methods: Study participants had ≥2 risk factors, consisting of age ≥75 years, female sex, obstructive sleep apnea, peripheral vascular disease, diabetes mellitus, obesity, hypertension, and congestive heart failure. Using the monitoring device, 30-second heart rhythm recordings were obtained on 4 different occasions. All tracings were reviewed by a cardiologist and, if uncertain, by an electrophysiologist. The nursing facility was notified of any diagnosis of AF, prompting further evaluation by the primary physician. Results: Of the 245 residents screened, 18 (7.4%) had a diagnostic tracing for AF, 15 (83.3%) of whom had AF on the initial screen. There were no significant differences in demographics or individual risk factors between residents with and those without AF. Conclusion: Intermittent ECG screening of high-risk nursing home residents using a simple, handheld device provided a diagnostic yield in our population comparable to that observed in past studies. Such screening of high-risk individuals can aid in the early diagnosis of AF and initiation of appropriate treatment.